Reminder: This post contains 2819 words
· 9 min read
· by Xianbin
This post presents basics about eigenvalues and eigenvectors.
Eigenvalues and Eigenvectors
For a matrix A ∈ C n × n A \in \mathbb{C}^{n\times n} A ∈ C n × n , scalars λ \lambda λ and vectors x n × 1 \mathsf{x}_{n\times 1} x n × 1 satisfying A x = λ x A\mathsf{x} = \lambda \mathsf{x} A x = λ x are eigenvalues and eigenvectors of A A A . The set of distinct eigenvalues, δ ( A ) \delta(A) δ ( A ) is the spectrum of A A A .
The characteristic polynomial of A n × n A_{n\times n} A n × n is p ( λ ) = det ( A − λ I ) p(\lambda) = \text{det}(A-\lambda \textup{I}) p ( λ ) = det ( A − λ I ) .
Let { x ≠ 0 ∣ x ∈ N ( A − λ I ) } \{ x \neq 0 \mid x \in N(A -\lambda \textup{I})\} { x = 0 ∣ x ∈ N ( A − λ I )} be the set of all eigenvectors associated with eigenvalues λ \lambda λ . We say that N ( A − λ I ) N(A - \lambda \text{I}) N ( A − λ I ) is the eigenspace for A A A .
Definition \textbf{Definition} Definition [Spanning Sets]. For a set of vectors S = { v 1 , … , v t } \mathcal{S} = \{v_1,\ldots, v_t\} S = { v 1 , … , v t } , the subspace
s p a n ( S ) = { α 1 v 1 + ⋯ + α t v t } span(\mathcal{S}) = \{\alpha_1v_1+\cdots+\alpha_t v_t\} s p an ( S ) = { α 1 v 1 + ⋯ + α t v t }
that forms all linear combinations of vectors of S \mathcal{S} S is called the space spanned by S \mathcal{S} S .
Symmetric Function s k s_k s k
We define the k k k -th symmetric function of λ 1 , λ 2 , … , λ n \lambda_1,\lambda_2,\ldots,\lambda_n λ 1 , λ 2 , … , λ n to be the sum of the product of eigenvalues multiplication for k k k times, i.e.,
s k = ∑ 1 ≤ i 1 < ⋯ < i k ≤ n λ i 1 … λ i k s_k = \sum_{1\leq i_1<\cdots<i_k \leq n}\lambda_{i_1}\ldots \lambda_{i_k} s k = 1 ≤ i 1 < ⋯ < i k ≤ n ∑ λ i 1 … λ i k
Example: n = 3 n = 3 n = 3
s 1 = λ 1 + λ 2 + λ 3 s_1 = \lambda_1 + \lambda_2 + \lambda_3 s 1 = λ 1 + λ 2 + λ 3
s 2 = λ 1 λ 2 + λ 1 λ 3 + λ 2 λ 3 s_2 = \lambda_1\lambda_2+\lambda_1\lambda_3 + \lambda_2\lambda_3 s 2 = λ 1 λ 2 + λ 1 λ 3 + λ 2 λ 3
s 3 = λ 1 λ 2 λ 3 s_3 = \lambda_1\lambda_2\lambda_3 s 3 = λ 1 λ 2 λ 3
We expand
p ( λ ) = det ( A − λ I ) = ∣ a 11 − λ a 12 ⋯ a 1 n a 21 a 22 − λ ⋯ a 2 n ⋮ ⋮ ⋯ ⋮ a n 1 a n 2 ⋯ a n n − λ ∣ p(\lambda) = \text{det}(A-\lambda\text{I})
=\left \lvert\begin{matrix}
a_{11}-\lambda & a_{12} &\cdots & a_{1n}\\
a_{21} & a_{22}-\lambda &\cdots &a_{2n}\\
\vdots & \vdots & \cdots & \vdots\\
a_{n1} & a_{n2}& \cdots & a_{nn}-\lambda
\end{matrix}
\right \rvert p ( λ ) = det ( A − λ I ) = ∣ ∣ a 11 − λ a 21 ⋮ a n 1 a 12 a 22 − λ ⋮ a n 2 ⋯ ⋯ ⋯ ⋯ a 1 n a 2 n ⋮ a nn − λ ∣ ∣
as follows.
p ( λ ) = ( − 1 ) n [ λ n + c 1 λ n − 1 + ⋯ + c n − 1 λ + c n ] p(\lambda) = (-1)^n[\lambda^n+c_1\lambda^{n-1}+\cdots+c_{n-1}\lambda+c_n] p ( λ ) = ( − 1 ) n [ λ n + c 1 λ n − 1 + ⋯ + c n − 1 λ + c n ]
By setting λ = 0 \lambda = 0 λ = 0 , we have:
Proposition 1: c n = ( − 1 ) n det ( A ) c_n = (-1)^n \text{det}(A) c n = ( − 1 ) n det ( A ) .
Now, let us see the value of c 1 c_1 c 1 .
p ( λ ) = ( a 11 − λ ) ⋯ ( a n n − λ ) + ∑ i = 2 n − 2 c i ′ λ n − i + c n ′ p(\lambda) = (a_{11}-\lambda)\cdots(a_{nn}-\lambda)+\sum_{i=2}^{n-2}c'_i\lambda^{n-i}+c'_n p ( λ ) = ( a 11 − λ ) ⋯ ( a nn − λ ) + i = 2 ∑ n − 2 c i ′ λ n − i + c n ′
It is easy to see that we only need to care about ( a 11 − λ ) ⋯ ( a n n − λ ) (a_{11}-\lambda)\cdots(a_{nn}-\lambda) ( a 11 − λ ) ⋯ ( a nn − λ ) to find c 1 c_1 c 1 .
We can see that there are n n n ways of obtaining ( − 1 ) n − 1 λ n − 1 (-1)^{n-1}\lambda^{n-1} ( − 1 ) n − 1 λ n − 1 .
Then
c 1 = ( − 1 ) n − 1 / ( − 1 ) n ⋅ ∑ i = 1 n a i i = − trace ( A ) c_1 = (-1)^{n-1}/(-1)^n \cdot \sum_{i=1}^n a_{ii} = -\text{trace}(A) c 1 = ( − 1 ) n − 1 / ( − 1 ) n ⋅ i = 1 ∑ n a ii = − trace ( A )
Next,
Theorem \textbf{Theorem} Theorem [The fundamental Theorem of Algebra]. If P ( x ) P(x) P ( x ) is a polynomial of degree, then the equation P ( x ) = 0 P(x) = 0 P ( x ) = 0 has exactly n n n roots.
By the above theorem,
p ( λ ) = ( − 1 ) n ( λ − λ 1 ) ⋯ ( λ − λ n ) = ( − 1 ) n [ λ n − λ n − 1 ∑ i = 1 n λ i + ⋯ + λ n − k ∑ ( i 1 , ⋯ , i k ) ∈ δ k ∏ j = 1 k λ i j ] \begin{align}
\begin{aligned}
p(\lambda) = (-1)^n(\lambda-\lambda_1)\cdots(\lambda-\lambda_n) \\
=(-1)^n\left[
\lambda^n - \lambda^{n-1}\sum_{i=1}^n \lambda_i+\cdots + \lambda^{n-k}\sum_{(i_1,\cdots,i_k) \in \delta_k}\prod_{j=1}^k \lambda_{i_j}
\right]
\end{aligned}
\end{align} p ( λ ) = ( − 1 ) n ( λ − λ 1 ) ⋯ ( λ − λ n ) = ( − 1 ) n ⎣ ⎡ λ n − λ n − 1 i = 1 ∑ n λ i + ⋯ + λ n − k ( i 1 , ⋯ , i k ) ∈ δ k ∑ j = 1 ∏ k λ i j ⎦ ⎤
So, c 1 = − ∑ i = 1 n λ i c_1 = -\sum_{i=1}^n \lambda_i c 1 = − ∑ i = 1 n λ i .
Since c 1 = − trace ( A ) c_1 = -\text{trace}(A) c 1 = − trace ( A ) , we obtain that
trace ( A ) = ∑ i = 1 n λ i \text{trace}(A) = \sum_{i=1}^n \lambda_i trace ( A ) = i = 1 ∑ n λ i
Also, we find that s k = ( − 1 ) k c k s_k =(-1)^k c_k s k = ( − 1 ) k c k .
∏ i = 1 n λ i = ( − 1 ) n c n \prod_{i=1}^n \lambda_i = (-1)^n c_n ∏ i = 1 n λ i = ( − 1 ) n c n .
By setting λ = 0 \lambda = 0 λ = 0 , we obtain
det ( A ) = ( − 1 ) n c n = ∏ i = 1 n λ i \text{det}(A) = (-1)^n c_n =\prod_{i=1}^n \lambda_i det ( A ) = ( − 1 ) n c n = i = 1 ∏ n λ i
Reference
[1]. Meyer, Carl D. Matrix analysis and applied linear algebra . Society for Industrial and Applied Mathematics, 2023.